Properties of SiO₂-GaAs and Au-Ti-SiO₂-GaAs structures used in production of transmission lines - Boltovets, N.S.; Kashin, G.N.; Konakova, R.V.; Lyapin, V.G.; Milenin, V.V.; Soloviev, E.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
We investigated electrophysical properties of the SiO₂-GaAs and Au-Ti-SiO₂-GaAs structures that are used in technological process when manufacturing transmission lines for microwave integrated circuits. The SiO₂-GaAs structures were formed using different techniques, namely, (i) monosilane oxidation in oxygen, (ii) high-temperature tetraethoxysilane decomposition, (iii) high-frequency cathode sputtering of quartz in argon plasma, and (iv) electron-beam evaporation of quartz in a vacuum. The SiO₂ films obtained using monosilane oxidation or electron-beam evaporation of quartz demonstrated better properties. For the Au-Ti-SiO₂-GaAs structures a layer structure transformation was shown to occur, with formation of TiOx-SiO₂ junction and gold atoms penetration over the whole adhesion layer thickness. The microwave oscillator modules made using the Au-Ti-SiO₂-GaAs (Si) structures demonstrated output power of 10-60 mW in the 8 mm wavelength range.